Edgewise vibration reduction of small size wind turbine blades using shunt damping. (24th September 2019) - Biglari, Hamed; Fakhari, Vahid
Edgewise vibration in wind turbine blades is one of the important factors that results in reducing the performance of wind turbines. Therefore, control or reduction of the mentioned vibrations can be of great help in increasing the efficiency of wind turbines. In this paper, the shunt damping method is proposed to reduce the edgewise blade vibration of horizontal axis wind turbines. For this purpose, partial differential equations governing dynamics of the system are derived using the Lagrange method. These equations are completely nonlinear and linearization is not performed to avoid possible errors in the analysis. In order to evaluate the effectiveness of the proposed shunt damping method in vibration reduction of the wind turbine blade, obtained results by applying shunt damping method are compared with corresponding results obtained by employing a conventional method known as a tuned mass damper (TMD). For better comparison, by considering proper cost functions, the shunt damper and TMD parameters are optimized using a genetic algorithm. Finally, the effectiveness of optimized shunt damper in vibration reduction of the blade is compared with optimized TMD by presenting simulation results.